2021
DOI: 10.1186/s12873-021-00472-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography indicators for predicting difficult intubation: a systematic review and meta-analysis

Abstract: Background Ultrasonography (US) is recently used frequently as a tool for airway assessment prior to intubation (endotracheal tube (ETT) placement), and several indicators have been proposed in studies with different reported performances in this regard. This systematic review and meta-analysis reviewed the performance of US in difficult airway assessment. Methods This systematic review and meta-analysis was conducted according to the guideline of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
2
26
0
4
Order By: Relevance
“…One intubation attempt suggests that intubation was easy even if the CL grade was 3 and 4. These findings are consistent with those of other studies (Huh et al, 2009;Prakash et al 2013;Kaleziã et al, 2016;Sotoodehnia et al, 2021), which reported that there were no patients with failed intubation. When the first attempt was unsuccessful, the intubation was performed by videolarygoscopy.…”
Section: Discussionsupporting
confidence: 93%
“…One intubation attempt suggests that intubation was easy even if the CL grade was 3 and 4. These findings are consistent with those of other studies (Huh et al, 2009;Prakash et al 2013;Kaleziã et al, 2016;Sotoodehnia et al, 2021), which reported that there were no patients with failed intubation. When the first attempt was unsuccessful, the intubation was performed by videolarygoscopy.…”
Section: Discussionsupporting
confidence: 93%
“…Heterogeneity among the studies is well described (44)(45)(46)(47)(48) and has hindered generalizing data on the efficacy of airway ultrasound. Heterogeneity exists in the available literature regarding patients, equipment, measurements, and thresholds among varying tests for predicting difficult laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis (data from 26 articles that had examined a total of 45 ultrasonography (US) indicators for predicting difficult intubation), Sotoodehnia et al, 14 found that the most common ultrasonography parameter was the "thickness of anterior neck soft tissue at the vocal cords level." Furthermore, "skin to epiglottis" and "anterior neck soft tissue at the hyoid bone level" were among the most common indicators examined in this area.…”
Section: Carried Outmentioning
confidence: 99%